Design of ancillary service markets and products: Challenges and recommendations for EU renewable power systems: Deliverable D3.3 - van der Welle, Adriaan (2022)
Project TradeRES - New Markets Design & Models for 100% Renewable Power Systems: https://traderes.eu/about/